Managing crop tradeoffs: A methodology for comparing the water footprint and nutrient density of crops for food system sustainability - Sokolow, J.; Kennedy, G.; Attwood, S. (Elsevier, 2019)
The relationship between human nutrition and the use of available resources to feed the planet's growing population demands greater attention from decision makers at all levels of governance. Indicators with dual environmental sustainability and food and nutrition security goals can encourage and measure progress towards a more sustainable food system. This article proposes a methodology that supports the development of an approach to assess the water footprint of nutrient-dense foods [m3/kg]. It provides a clear explanation of the methodology, and the use of water footprint benchmark data and corresponding United States Department of Agriculture (USDA) nutrient composition data to apply the process. The study analyzed data for 17 grains, roots and tubers, 9 pulses, 10 nuts and seeds, 17 vegetables, and 27 fruits. Of these, fruits and vegetables are 85% of the bottom quartile for water footprint (i.e., highly water efficient) and 100% of the top quartile for nutrient-density (i.e., very nutrient dense). Spinach is a clear winner, with a very high nutrient-density and low water footprint. The article proposes that this approach can help to establish broad typologies to guide decision makers in distinguishing between win-win, win-lose, and lose-lose scenarios of natural resource use and nutrition security. This resource, if considered along with contributing social, environmental, and economic factors (e.g., local tastes, available water resources, soil fertility, local economies) can promote a food system that offers a diverse range of nutrient-dense foods more sustainably.